2013
DOI: 10.3732/ajb.1200646
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Cypripedium calceolus (Orchidaceae) seeds analyzed by attenuated total reflectance IR spectroscopy: In search of understanding longevity in the ground

Abstract: We suggest that degradation of lignin and enrichment of the testa surface with CaCO3 are important stimulants of germination both in the habitat and during laboratory sowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 32 publications
(40 reference statements)
2
35
0
2
Order By: Relevance
“…, Barsberg et al . ). Very little is known about dormancy in epiphytic orchids, but Kartzinel et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Barsberg et al . ). Very little is known about dormancy in epiphytic orchids, but Kartzinel et al .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, almost all the accounts of dormancy (or relatively lack thereof) involve temperate, terrestrial orchids (Whigham et al 2006, Barsberg et al 2013. Very little is known about dormancy in epiphytic orchids, but Kartzinel et al (2013) found that 40 percent of the seeds desiccated or decayed within 5 months, and that habitat was the prime factor influencing recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…The samples stained with CBB and PAS demonstrate the accumulation of proteins and starch during the stages analyzed ( Figure 2L and 2M). These reserves were also observed using FTIR spectrophotometry (Figure 4), which has been previously used to analyze the composition of seeds (Kuhnen et al, 2010;Amir, Anjum, Khan, Khan, Pasha, & Nadeem, 2013;Barsberg, Rasmussen, & Kodahl, 2013;Araldi, Coelho, & Maraschin, 2016). Lipids, starch, proteins and phenolic compounds were present in all seed samples.…”
Section: Discussionmentioning
confidence: 99%
“…), and it has also been suggested that ligninases in soil could facilitate seed germination by essentially scarifying the seed coat (Barsberg et al . ). Indeed, the evolution of ligninolytic peroxidases was one of the fundamental events driving the early co‐evolution of fungi and woody plants from the Permian onwards (Martin et al .…”
Section: Introductionmentioning
confidence: 97%
“…The location of lignin as a cell wall component in both inner and outer seed integuments is particularly well studied in a range of orchid species, and several contrasting methods not only confirm the presence of lignin but also provide a detailed picture of where and when lignin is synthesised, usually during the final stages of seed development resulting in ‘browning’ of the seeds (Yamazaki & Miyoshi ; Barsberg et al . ; Rao et al . ; Yang & Lee ).…”
Section: Introductionmentioning
confidence: 99%